Prognostic value of preoperative systemic inflammation response index in patients with oral squamous cell carcinoma: Propensity score‐based analysis. Issue 11 (18th July 2020) - Lin, Jing; Chen, Lin; Chen, Qing; Zhuang, Zhaocheng; Bao, Xiaodan; Qian, Jiawen; Hong, Yihong; Yan, Lingjun; Lin, Lisong; Shi, Bin; Qiu, Yu; Pan, Lizhen; et al.
Abstract: Background: The aim of the study was to elucidate the relationship between systemic inflammation response index (SIRI) and the prognosis of postoperative oral squamous cell carcinoma (OSCC) patients. Methods: The prognostic value of SIRI was evaluated in a prospective cohort consisting of 535 OSCC patients with surgical resection. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) analyses were used to further verify the prognostic value of SIRI. Results: Patients with a higher SIRI had a significantly increased risk of mortality compared with those with a low SIRI (HR [hazard ratio]: 1.60, 95% CI [confidence interval]: 1.04‐2.47). The similar association pattern was observed following PSM (HR: 1.97, 95% CI: 1.14‐3.40) and IPTW (HR: 1.70, 95% CI: 1.29‐2.24) analyses. Of note, receiving postoperative chemotherapy resulted in a 72% of decreased risk of death among patients with a higher SIRI (HR: 0.28, 95% CI: 0.08‐0.95). Additionally, a novel prognostic nomogram, based on TNM stage, tumor differentiation, and SIRI, demonstrated superior accuracy for the prediction of overall survival than that of the seventh edition of the AJCC staging system. Conclusion: Preoperative SIRI may be a valuable tool for prediction of survival of OSCC patients.